Pediatric Magnet Ingestion with Delayed Presentation: Case Series from Tertiary Center in Saudi Arabia - Alareefy A; Barnawi E; Alrashed R; Alamri A; Aleidan AM; Alghofaily M; Alkhelaif M; Kanfar S (Dove Medical Press, 2023)
Abdulaziz Alareefy,1 Esam Barnawi,1 Rawan Alrashed,1 Abdulelah Alamri,1 Ahmed M Aleidan,2 Mazen Alghofaily,3 Mayada Alkhelaif,3 Sara Kanfar4 1Pediatric Emergency Department, King Fahad Medical City, Riyadh Second Health Cluster, Riyadh, Saudi Arabia; 2Pediatric Pulmonology Department, King Fahad Medical City, Riyadh Second Health Cluster, Riyadh, Saudi Arabia; 3General Pediatric Department, King Fahad Medical City, Riyadh Second Health Cluster, Riyadh, Saudi Arabia; 4Pediatric Surgery Department, King Fahad Medical City, Riyadh Second Health Cluster, Riyadh, Saudi ArabiaCorrespondence: Abdulaziz Alareefy, Pediatric Emergency Department, King Fahad Medical City, Central Second Health Cluster, Ministry of Health, P.O. Box. 59046, Riyadh, 11525, Saudi Arabia, Email aalareefy@kfmc.med.saAbstract: Swallowing foreign bodies is common in young kids, especially those aged 6 months to 6 years. Magnet ingestion is a hazardous health issue that extremely jeopardizes the most vulnerable group, children, to risks of intestinal obstruction and worse, perforation. We, hereby, report 3 cases of magnet ingestion in the pediatric age group who had multiple beaded magnets stuck inside their GI tract over a variable period of 1 to 10 months before their presentation to the Emergency Department, King Fahad Medical City Riyadh, Saudi Arabia.Keywords: magnet ingestion, pediatric, emergency, foreign body, Saudi Arabia